Good practices with injectables: digital technology for nursing education to control infections - Roseira, Camila Eugenia; Fittipaldi, Thais Roberto Magalhães; Costa, Lívia Cristina Scalon da; Silva, Darlyani Mariano da; Dias, Ana Angélica Lima; Figueiredo, Rosely Moralez (Universidade Federal de São Carlos, 2022)
Objectives: to build, validate, implement, and evaluate an educational strategy for nursing professionals and students aiming at good practices in administrating injectable medications. Methods: methodological study for the development of an open course, without tutoring, in a virtual learning environment about good practices with injectable medications. Results: ten evaluators validated the educational material that supported the course “Good Practices with Injectables: actions for infection control” regarding objectives, structure, and relevance for the e-book and podcast. The evaluation by the target population (17 individuals) suggests that it is relevant and motivating. However, the forum may be the least attractive tool, and other studies should be conducted to identify its effectiveness as a tool for content retention in open courses. Conclusions: the course is open and has no mentoring for students and nursing professionals with validated educational material for this purpose may be used for nursing education in formal or informal settings.
Boas práticas com injetáveis: tecnologia digital para educação em enfermagem visando ao controle de infecções
Buenas prácticas con inyectables: tecnología digital para educación en enfermería visando al control de infecciones
Keywords: Education; Nursing; Nursing care; Infection control; Educational Technology; Injections; Intravenous; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS